The convivial and the pastoral in patient–doctor relationships: a multi‐country study of patient stories of care, choice and medical authority in cancer diagnostic processes - MacArtney, JI; Andersen, RS; Malmström, M; Rasmussen, B; Ziebland, S (Wiley, 2020)
Experiences of cancer diagnosis are changing in light of both the increasingly technological-clinical diagnostic processes and the socio-political context in which interpersonal relations take place. This has raised questions about how we might understand patient-doctor relationship marked by asymmetries of knowledge and social capital, but that emphasise patients' empowered choices and individualised care. As part of an interview study of 155 participants with bowel or lung cancer across Denmark, England and Sweden, we explored participants' stories of the decisions made during their cancer diagnostic process. By focusing on the intersections of care, choice and medical authority - a convivial pastoral dynamic - we provide a conceptual analysis of the normative ambivalences in people's stories of their cancer diagnosis. We found that participants drew from care, choice and medical authority to emphasise their relationality and interdependence with their doctors in their stories of their diagnosis. Importantly negotiations of an asymmetrical patient-doctor relationship were part of an on-going realisation of the healthcare processes as a human endeavour. We were therefore able to draw attention to the limitations of dichotomising emancipatory-empowerment discourses and argue for a theorisation of the patient-doctor relationship as a contextually bounded and relationally ambivalent humanity.